A dual-heterostructure dysprosium-containing magnesium alloy and a preparation method thereof
Patent Information
- Application Number
- CN202611340414.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明所要解决的技术问题是,克服上述背景技术中变形镁合金在高强度和大塑性方面不可兼得的技术劣势,通过优选合金化元素及其添加量辅以针对性的制备工艺设计,获得高强度和大塑性兼备的高性能变形镁合金
1.通过低成本和短流程实现镁合金强度与塑性的协同提升:本发明以Al为主要合金化元素并添加0.8-1.2 wt.% Yb作为核心合金化元素,低于高稀土含量镁合金中的稀土添加量。借助精准的常规工艺组合,即熔炼、固溶和慢速挤压完成了独特双异质结构的构筑。该结构凭借细晶区、多尺度第二相以及背应力的协同强化,获得了高强度。同时借助弱织构和非基面滑移活性提升以及粗晶区的容纳位错能力,保障了高塑性,以此突破了传统镁合金强度与塑性难以兼得的传统难题;
Smart Images

Figure CN122898776A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a Mg-Al-Yb-Zn magnesium alloy that combines high strength and high plasticity, and whose microstructure features alternating distribution of coarse and fine grain regions and preferred distribution of second phases at multiple scales. Background Technology
[0002] Magnesium alloys, as the lightest metallic structural materials, have long faced the challenge of simultaneously achieving high strength and high ductility, a key issue for their large-scale application. While microstructure can be controlled through alloying and plastic processing to improve certain properties, common alloying elements and processing techniques still have limitations in improving the synergy between strength and ductility. First, regarding the control of grain size and structure, traditional hot deformation processes often result in a relatively uniform recrystallized structure. While this unidirectional structure helps improve ductility, it is difficult to introduce a high level of back stress strengthening effect, making it difficult to improve strength. Second, in terms of second-phase control, existing alloying systems and deformation processing methods often result in a uniformly dispersed or randomly distributed second phase. This second-phase configuration cannot effectively synergize with the grain structure in terms of spatial distribution, and its relatively uniform size and morphology make it difficult to construct multi-layered heterogeneous interfaces. This limits the role of the second phase in controlling dislocation movement, coordinating strain, and inducing back stress. Finally, regarding the synergy between process and microstructure, conventional process parameter design primarily focuses on improving formability and productivity, lacking a clear objective of actively constructing a dual heterogeneous structure of "grains" and "second phase" through precise control of thermodynamic and kinetic conditions. This prevents the advantages of alloy composition design from being translated into the desired ideal microstructure and strength-plasticity balance through process optimization. Therefore, it is urgent to leverage the optimal selection of alloy composition and the matching of precise preparation processes to actively construct a dual heterogeneous structure in magnesium alloys with synergistically optimized spatial distribution of grains and the second phase, thereby fundamentally overcoming the balance problem of the mutual constraint between strength and plasticity. Summary of the Invention
[0003] The purpose of this invention is to provide a wrought magnesium alloy that achieves a synergistic improvement in high strength and high plasticity through a dual heterogeneous structure of grains and a second phase.
[0004] The technical problem this invention aims to solve is to overcome the inherent disadvantage of wrought magnesium alloys in the prior art, where high strength and high plasticity are mutually exclusive. By optimizing alloying elements and their amounts, coupled with targeted preparation process design, a high-performance wrought magnesium alloy exhibiting both high strength and high plasticity can be obtained. The extruded magnesium alloy prepared using this method exhibits a room-temperature tensile yield strength of not less than 220 MPa, a tensile strength of not less than 330 MPa, and an elongation after fracture of not less than 25% along the extrusion direction. This alloy demonstrates excellent properties, the preparation method requires readily available raw materials, has a short process flow, and uses conventional equipment, making it suitable for applications in aerospace, transportation, and electronics. It has promising application prospects in fields such as semiconductor manufacturing.
[0005] The objective of this invention is achieved through the following technical solution: First, the alloying elements and their amounts are carefully selected. During the smelting stage, the strong compositional supercooling effect of Al in the magnesium melt is fully utilized to promote the formation of an equiaxed, refined, and uniformly sized as-cast microstructure, optimizing the initial as-cast grain morphology. Simultaneously, Yb participates in the formation of the thermally stable Al3Yb phase, providing a microstructural basis for second-phase control during subsequent hot deformation. Subsequently, high-temperature, long-term solidification under inert gas protection promotes the formation of low-melting-point Mg... 17 Al 12 The second phase dissolves back into the matrix, eliminating the coarse compounds covering the grain boundaries, leaving only a portion of the thermally stable Al3Yb phase. Finally, isothermal slow hot extrusion at a moderate extrusion temperature and a large extrusion ratio is performed to fully initiate the dynamic recrystallization process, thoroughly refining the solid solution microstructure and consuming deformed dislocations, ultimately obtaining a well-recrystallized dual heterostructure microstructure. During this process, the large extrusion ratio and prolonged high-temperature deformation promote the complete breakup and refinement of the remaining coarse Al3Yb phase, aligning it along the extrusion direction. This facilitates local dynamic recrystallization nucleation through particle-induced nucleation (PSN) mechanism. Simultaneously, submicron-sized Mg... 17 Al 12 The phase preferentially precipitates dynamically along high-density grain boundaries, pinning the grain boundaries and inhibiting the growth of fine grains formed by PSN, gradually evolving into banded fine-grained regions; while the regions between the fine-grained regions lack large-sized Al3Yb phase to promote nucleation and submicron Mg. 17 Al 12The grain boundary pinning effect of the phase allows for the nucleation and growth of dynamically recrystallized grains at a relatively uniform rate. However, as they extend to the fine-grained region boundary, they encounter significant resistance, gradually forming a coarse-grained region and a heterogeneous interface, ultimately resulting in a dual heterogeneous structure with varying grain size and second-phase distribution. Sufficient dynamic recrystallization promotes the full growth of non-basal grains, further suppressing the formation of strong basal texture. During subsequent tensile deformation, the fine-grained region in this dual heterogeneous structure effectively provides fine-grained strengthening, second-phase strengthening, and back stress strengthening, significantly improving the alloy's strength. Meanwhile, the weakened and tilted basal texture enhances the activity of various slip systems during deformation, promoting strain homogenization. Furthermore, the coarse-grained region better accommodates dislocations, while the fine grains and second phase in the fine-grained region improve local deformation coordination, thereby improving elongation after fracture. Finally, the technical solution of this invention successfully prepared a wrought magnesium alloy material with both high strength and high plasticity.
[0006] The specific technical solution is as follows: A ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized in that the alloy comprises, by mass percentage: Al 7.5-8.5%, Yb 0.8-1.2%, Zn 0.4-0.6%, with the balance being Mg and other unavoidable impurities; the dynamic recrystallization degree of the extruded microstructure of the alloy is greater than 85%, and the dynamic recrystallization degree is obtained statistically from EBSD orientation imaging data; on the longitudinal section of the extruded material, coarse-grained and fine-grained regions are alternately distributed radially and extend along the extrusion direction, with the average grain size of the coarse-grained region being 6-8.5 μm and the average grain size of the fine-grained region being 2-5 μm; the second phase comprises a blocky Al3Yb phase and spherical Mg. 17 Al 12 Phases and spherical Mg2Yb phases, including Al3Yb phase and Mg 17 Al 12 The number density of the Mg2Yb phase is higher in the fine-grained region than in the coarse-grained region, and the Mg2Yb phase is discretely distributed in both the coarse-grained and fine-grained regions; the number density can be obtained statistically from SEM or TEM images of the longitudinal section of the extruded material; the room temperature tensile yield strength of the alloy along the extrusion direction is not less than 220 MPa, the tensile strength is not less than 330 MPa, and the elongation after fracture is not less than 25%. Furthermore, a ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized in that: the as-cast alloy consists of α-Mg grains and island-like Mg particles covering the grain boundaries. 17 Al 12 The alloy consists of phases, including Al3Yb phases dispersed at grain boundaries and within grains. The grain size of the as-cast alloy is 160-180 μm. The solid-solution alloy has clear grain boundaries, and no coarse Mg phases were detected. 17 Al 12The phase consists of an irregularly shaped Al3Yb phase discretely distributed in the solid solution state, with a grain size of 170-200 μm. The extruded microstructure is characterized by an Al3Yb phase size of 150 nm-2 μm, and the Mg... 17 Al 12 The phase size is 100-500 nm, and the Mg2Yb phase size is 10-50 nm; the extruded alloy exhibits a weak tilted basal surface texture, which means that the basal surface poles are deflected relative to the extrusion direction and the maximum pole density value is 5.5-6.5 mud.
[0007] Furthermore, when the ytterbium-magnesium alloy is subjected to cyclic loading, unloading, and reloading tensile tests along the extrusion direction at room temperature, the maximum heterogeneous deformation-induced stress (traditionally also known as back stress) is 170–185 MPa. The heterogeneous deformation-induced stress is calculated based on the loading, unloading, and reloading hysteresis loops, using the formula σ. HDI =(σ u +σ r ) / 2, where σ u To unload the yield stress, σ r To reapply yield stress, the specific test conditions and yield point criteria are determined according to the test method described in the specific implementation method.
[0008] Furthermore, the preparation method of the ytterbium-containing magnesium alloy includes the following steps: 1) Alloy smelting: Magnesium ingots are heated and melted in a resistance heating furnace under the protection of SF6 and CO2 mixed gas. Then, pure aluminum ingots are added at 700-710 ℃ according to the mass percentage of Al in the final alloy of 7.5-8.5%. The mixture is stirred for 3-5 min under flux protection to aid melting. Then, Mg-Yb master alloy is added at 720-725 ℃ according to the mass percentage of Yb in the final alloy of 0.8-1.2%. Finally, zinc ingots are added at 700-710 ℃ according to the mass percentage of Zn in the final alloy of 0.4-0.6%. The mixture is stirred for 3-5 min to aid melting. The mixture is held at 720-725 ℃ for 5-10 min, a covering agent is added, and the mixture is allowed to stand to allow the inclusions to settle. After standing at 700-710 ℃ for 5-10 min, the slag is removed and the ingots are cast. 2) Solution treatment: The above ingots are held at 420-430 ℃ for 23-25 h under argon protection, and then cooled to room temperature by water after being taken out of the furnace; 3) Slow isothermal extrusion: Heat the solution-treated billet to 295-300 ℃ and hold for 30 min. Then, perform isothermal hot extrusion at a speed of 0.5-1 mm / s with an extrusion ratio of 20:1. After the extruded material is extruded from the mold, it is cooled to room temperature with water.
[0009] Compared to existing magnesium alloy materials, the advantages of this material and its preparation method are as follows: 1. Achieving Synergistic Improvement of Strength and Plasticity in Magnesium Alloys through Low Cost and Short Process: This invention uses Al as the main alloying element and adds 0.8-1.2 wt.% Yb as the core alloying element, which is lower than the rare earth addition amount in high rare earth content magnesium alloys. A unique dual heterogeneous structure is constructed through a precise combination of conventional processes, namely melting, solution treatment, and slow extrusion. This structure achieves high strength through the synergistic strengthening of fine-grained regions, multi-scale second phases, and back stress. Simultaneously, high plasticity is ensured by enhancing the activity of weak texture and non-basal slip, as well as the dislocation-accommodating capacity of the coarse-grained region, thus overcoming the traditional challenge of achieving both strength and plasticity in magnesium alloys. 2. Synergistic Regulation of Multi-Scale Second Phase and Texture Evolution by Yb Addition: During alloy solidification, Yb preferentially combines with Al to form the thermally stable Al3Yb phase. This phase can be partially retained even after prolonged solution treatment and undergoes fragmentation and refinement during subsequent hot extrusion, providing favorable conditions for particle-stimulated nucleation (PSN). Solution treatment promotes the growth of coarse Mg at the as-cast grain boundaries. 17 Al 12 Phase re-dissolution, followed by subsequent hot extrusion, yields submicron-sized Mg. 17 Al 12 The phase dynamically precipitates near high-density grain boundaries, while the nanoscale Mg2Yb phase is dispersed in the extruded matrix. Submicron to micron-sized Al3Yb phase and submicron-sized Mg2Yb phase are also present. 17 Al 12 The Al3Yb phase and the nanoscale Mg2Yb phase together constitute a multi-scale second-phase system, in which the Al3Yb phase and Mg 17 Al 12 The number density of the second phase is higher in the fine-grained region than in the coarse-grained region. This spatial distribution characteristic, combined with the alternating distribution of coarse and fine-grained regions, is beneficial for improving the alloy's heterogeneous deformation-induced strengthening ability. Simultaneously, the addition of Yb and the corresponding microstructure evolution help weaken and tilt the basal texture, thereby improving the alloy's plastic deformation capacity.
[0010] 3. This invention provides a simple and efficient route for preparing high-performance magnesium alloys: Compared to costly and lengthy processes relying on complex and intense plastic deformation, such as equal-channel angular extrusion, or high-rare-earth-addition techniques, this invention utilizes conventional melting and casting, heat treatment, and extrusion equipment, resulting in a simpler process, shorter flow, and lower energy consumption. By precisely controlling the key process window of "medium temperature - slow speed - large extrusion ratio," the desired dual heterostructure can be stably and repeatedly induced. This method employs conventional melting and casting, solution treatment, and hot extrusion equipment, resulting in a shorter process flow.
[0011] 4. Comparative examples verified the necessity of Yb-induced dual heterostructure: In the Mg-8.0Al-0.5Zn alloy without Yb but using the same solution treatment and extrusion regime, the extruded microstructure mainly consisted of uniform equiaxed grains with an average grain size of 9.28 μm. The second phase was generally dispersed, without alternating coarse and fine grain regions or multi-scale selective distribution of the second phase. Compared with this comparative example, Example 1, while maintaining an elongation after fracture of over 20%, increased the yield strength and tensile strength from 167 MPa and 283 MPa to 230 MPa and 340 MPa, respectively. This indicates that the multi-scale second phase formed by Yb and the dual heterostructure it induces are beneficial to improving the strength-ductility matching ability of magnesium alloys. Attached Figure Description
[0012] Figure 1 The microstructure and property characteristics of the Mg-8.0 Al-1.0 Yb-0.5 Zn alloy prepared using the technology described in this application; Figure 1 a is the metallographic structure of the alloy in the as-cast state; 1b is the SEM and EDS surface scan of the as-cast state; 1c is the grain orientation distribution diagram and the average grain size statistics of coarse grains (CG) and fine grains (FG) in the extruded state; 1d is the metallographic structure of the longitudinal section of the extruded state; 1e is the SEM and EDS surface scan of the longitudinal section of the extruded state; 1f is the pole figure and inverse pole figure of the longitudinal section of the extruded state. Figure 2 TEM images of three typical second phases in the Mg-8.0 Al-1.0 Yb-0.5 Zn alloy prepared using the technology described in this application are shown below. Figure 2 a represents the typical Al3Yb phase TEM morphology and its corresponding high-resolution (TEM) Figure 2 a1) and Fourier transform graph ( Figure 2 a2), Figure 2 b is typical Mg 17 Al 12 Phase TEM morphology and its corresponding high resolution ( Figure 2 b1) and Fourier transform graph ( Figure 2 b2), Figure 2 c represents the typical TEM morphology of the Mg2Yb phase and its corresponding high-resolution (TEM) Figure 2 c1) and Fourier transform graph ( Figure 2 c2); Figure 2 d is a high-resolution image of the interface between a typical Al3Yb phase and the α-Mg matrix; Figure 2 e is typical Mg 17 Al 12 High-resolution image of the interface between the phase and the α-Mg matrix; Figure 2 f is a high-resolution image of the interface between a typical Mg2Yb phase and the α-Mg matrix.
[0013] Figure 3Typical cyclic loading mechanical properties of the Mg-8.0 Al-1.0 Yb-0.5 Zn alloy prepared using the technology described in this application are shown. Figure 3 a represents the cyclic loading and unloading curve of the extruded alloy. Figure 3 b represents the mechanical property curve under extrusion.
[0014] Figure 4 The images show the as-cast metallographic structure (4a), as-cast SEM and elemental EDS surface scan (4b), extruded grain orientation distribution (4c), extruded metallographic structure (4d), extruded longitudinal section SEM and elemental EDS surface scan (4e), and extruded longitudinal section pole figure and inverse pole figure (4f) of the Mg-7.5 Al-0.8 Yb-0.4 Zn alloy prepared using the technology of this application.
[0015] Figure 5 The images show the as-cast SEM and elemental EDS surface scans (5a), extruded grain orientation distribution (5b), extruded longitudinal section SEM and elemental EDS surface scans (5c), and extruded longitudinal section pole figure and inverse pole figure (5d) of the Mg-8.5 Al-1.2 Yb-0.6 Zn alloy prepared using the technology of this application. Detailed Implementation
[0016] The present invention will be specifically described below through embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.
[0017] Methods for calculating stress induced by cyclic loading, unloading, and reloading tests and heterogeneous deformation: Cyclic loading, unloading, and reloading tensile tests were conducted at room temperature. Tensile specimens were sampled along the extrusion direction, with a total length of 41.5 mm, a clamping section width of 6 mm, a thickness of 2 mm, a parallel section length of 17.5 mm, a width of 3 mm, and a transition radius of 10 mm. Testing was performed using a CMT5504 universal testing machine, with the tensile direction parallel to the alloy's extrusion direction.
[0018] During the test, strain control mode was used in both the loading and reloading phases, with the strain rate set to 1×10⁻⁶. -3 s -1 The engineering strain ε measured by the extensometer e According to ε t =ln(1+ε e Converted to true strain ε t Engineering stress σ e According to σ t =σ e (1+εe Convert to actual stress σ t The specimen was first loaded to 1% of the target true strain, then switched to force control mode at 500 N·min. -1 The unloading rate will unload the load to 100 N. After unloading to the target load, immediately switch to the response variable control mode at 1×10 -3 s -1 The strain rate was reloaded until the load level before unloading was restored, and then loading continued to the next target true strain. This unloading and reloading process was repeated at true strains of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%. Each completed unloading and reloading cycle was counted as one cycle, and each specimen underwent 15 cycles, with a maximum cycle true strain of 15%. The unloading amplitude was not expressed as a fixed strain amplitude, but was determined by the difference between the peak load at the start of each cycle and the 100 N termination load.
[0019] The induced stress of heterogeneous deformation is calculated based on the loading, unloading, and reloading hysteresis loops obtained from each cycle. For each hysteresis loop, an approximately linear elastic segment after the initial stress relaxation section of the unloading curve is first selected for linear fitting, and the resulting slope is defined as the effective unloading elastic modulus E. u Since the microstructure changes of the specimen during a single unloading and reloading process are negligible, the effective reloading elastic modulus E r Let it be E u Along the unloading direction, when the slope of the tangent line of the unloading curve is relative to E... u When the yield is reduced by 5%, the corresponding point is determined as the unloading yield point, and the actual stress at this point is denoted as the unloading yield stress σ. u Along the reloading direction, when the slope of the tangent to the reloading curve is relative to E r When the yield is reduced by 5%, the corresponding point is determined as the reload yield point, and the actual stress at this point is denoted as the reload yield stress σ. r σ u and σ r The same 5% slope reduction criterion was used for determination.
[0020] The heterogeneous deformation-induced stress σHDI corresponding to each cycle is calculated according to the following formula: σ HDI =(σ u +σ r ) / 2 In the formula, σ u To unload the yield stress, σ r To determine the reload yield stress, calculate the σ corresponding to each cycle within the range of 1% to 15% of the true strain. HDIThe maximum value among these values is taken as the maximum heterogeneous deformation-induced stress of the specimen. Unless otherwise stated, the maximum heterogeneous deformation-induced stress described in the specification and examples is obtained according to the above method.
[0021] Example 1
[0022] A ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized by the following composition by mass percentage: Al content 8.0%, Yb content 1.0%, Zn content 0.5%, and the balance being Mg and other unavoidable impurities; the extruded microstructure of the alloy exhibits a dynamic recrystallization degree of 91.3%, and on the longitudinal section of the extruded material, coarse-grained and fine-grained regions are alternately distributed radially and extend along the extrusion direction (e.g., ...). Figure 1 c. Figure 1 d and Figure 1 As shown in e); simultaneously, the bulk Al3Yb phase with a size ranging from submicron to micron ( Figure 1 e, Figure 2 a) and submicron-sized spherical Mg 17 Al 12 Mutually( Figure 1 e, Figure 2 b) Mainly distributed in fine-grained regions (such as...) Figure 1 d and Figure 1 As shown in e), the nanoscale spherical Mg2Yb phase is discretely distributed ( Figure 2 c); The alternating distribution of coarse and fine grain regions and the non-uniform distribution of the second phase create a dual heterogeneous synergistic effect, giving the alloy a significant back stress strengthening effect ( Figure 3 a); The Mg-Al-Yb-Zn alloy, after isothermal hot extrusion at 300 ℃ and an extrusion speed of 0.5 mm / s with an extrusion ratio of 20:1, exhibits a room temperature tensile yield strength of 230 MPa, a tensile strength of 340 MPa, and an elongation after fracture of 28.5%. Figure 3 b).
[0023] Furthermore, a ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized in that: the as-cast alloy consists of α-Mg grains and island-like Mg particles covering the grain boundaries. 17 Al 12 The composition includes the Al3Yb phase dispersed at grain boundaries and within grains. Figure 1 a and Figure 1 b) The average grain size of the as-cast alloy is 166 μm; the grain boundaries of the solid-solution alloy are clear, and no coarse Mg was detected. 17 Al 12 The phase consists of irregularly shaped Al3Yb phases discretely distributed in the solid solution alloy, with an average grain size of 191 μm; the extruded microstructure has an average grain size of 6.90 μm in the coarse-grained region and 3.97 μm in the fine-grained region. Figure 1 c); The extruded structure contains blocky Al3Yb phases with an average size of 1 μm enriched in the fine-grained region ( Figure 2 a, Figure 2 a1 and Figure 2 a2) and spherical Mg with an average size of 100 nm 17 Al 12 Mutually( Figure 2 b, b1 and b2), and spherical Mg2Yb phases with an average size of 15 nm discretely distributed in the coarse and fine grain regions (b, b1 and b2), as well as spherical Mg2Yb phases with an average size of 15 nm discretely distributed in the coarse and fine grain regions. Figure 2 c, c1, and c2); the extruded alloy exhibits a weak tilted basal texture, with a maximum extreme density of 6.42 MUD ( Figure 1 f) The extruded alloy was tested according to the above-described cyclic loading, unloading, and reloading test method. The tensile direction was parallel to the extrusion direction, and a total of 15 loading, unloading, and reloading cycles were performed within the range of 1% to 15% of the true strain. The induced stress of heterogeneous deformation was calculated based on each hysteresis loop, and the obtained σ HDI The stress increases with increasing actual strain, and the maximum heterogeneous deformation-induced stress within the tested cyclic range is 180 MPa. Figure 3 As shown in a.
[0024] HRTEM analysis results show that the (011) crystal plane of the Al3Yb phase forms a semi-coherent interface with the (000-2) crystal plane of the α-Mg matrix, with an interfacial mismatch of approximately 11.94%. Figure 2 As shown in d; Mg 17 Al 12 The phase forms a coherent interface with the α-Mg matrix, wherein Mg 17 Al 12 The mismatch between the (1-41) crystal plane of the phase and the (01-1-1) crystal plane of the α-Mg matrix is approximately 2.2%, such as Figure 2 As shown in e; the Mg2Yb phase and the α-Mg matrix do not form a continuous lattice matching relationship, and they form a non-coherent interface, such as... Figure 2 As shown in f. The above results indicate that the three typical second phases form semi-coherent, coherent, and incoherent interfaces with the α-Mg matrix, respectively, reflecting the differences in interface structure between the different second phases and the matrix.
[0025] In this embodiment, the formation of the dual heterostructure is mainly related to the Al3Yb phase and Mg. 17 Al 12 The size and spatial distribution of the phase are related. During hot extrusion, larger Al3Yb particles break down and become finer, and the particle-stimulated nucleation promotes dynamic recrystallization in the surrounding area; near the high-density grain boundaries formed by dynamic recrystallization, submicron-sized Mg... 17 Al 12The Al3Yb phase preferentially precipitates and restricts recrystallized grain growth through grain boundary pinning. Al3Yb and Mg phases... 17 Al 12 The concentrated distribution of the second phase in localized areas promotes the formation of fine-grained regions, while regions with relatively low second-phase density form larger recrystallized grains. Thus, the longitudinal section of the extruded material exhibits a dual heterogeneous structure with alternating coarse-grained and fine-grained regions, accompanied by selective distribution of the second phase. The different interfacial relationships between the three types of second phases and the α-Mg matrix provide a structural basis for analyzing the interfacial interactions between particles and the matrix, but are not the sole cause of the dual heterogeneous structure.
[0026] Furthermore, the preparation steps of this dual heterostructure ytterbium-magnesium alloy include the following: 1) Alloy smelting: Magnesium ingots are heated and melted in a resistance heating furnace under the protection of SF6 and CO2 mixed gas. Then, pure aluminum ingots are added at 710 ℃ according to the mass percentage of Al in the final alloy of 8%. The mixture is stirred for 4 min under flux protection to aid melting. Then, Mg-Yb master alloy is added at 725 ℃ according to the mass percentage of Yb in the final alloy of 1.0%. Finally, zinc ingots are added at 710 ℃ according to the mass percentage of Zn in the final alloy of 0.5%. The mixture is stirred for 5 min to aid melting. The mixture is held at 720 ℃ for 10 min, a covering agent is added, and the mixture is allowed to stand to allow the inclusions to settle. The mixture is then allowed to stand at 700 ℃ for 10 min, the slag is removed, and the ingots are cast. 2) Solution treatment: The above ingots are held at 420 ℃ for 24 h under argon protection, and then cooled to room temperature by water after being taken out of the furnace; 3) Slow isothermal extrusion: The solution-treated billet is heated to 300 ℃ and held for 30 min. The billet is then subjected to isothermal hot extrusion at a speed of 0.5 mm / s with an extrusion ratio of 20:1. Before extrusion, the difference between the surface temperature of the billet and the set temperature of the extrusion cylinder is measured by an infrared thermometer and is no more than 5 ℃. After the extruded material is extruded from the mold, it is immediately water-cooled to room temperature.
[0027] Example 2
[0028] A ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized by the following composition by mass percentage: Al 7.5%, Yb 0.8%, Zn 0.4%, with the balance being Mg and other unavoidable impurities; the extruded microstructure of the alloy exhibits a dynamic recrystallized grain area fraction of 93.7%, and on the longitudinal section of the extruded material, coarse-grained and fine-grained regions are alternately distributed radially and extend along the extrusion direction (e.g., ...). Figure 4 c. Figure 4 d and Figure 4 (as shown in e); simultaneously, there are bulk Al3Yb phases with sizes ranging from submicron to micron and submicron-sized spherical Mg... 17 Al 12 Mutually( Figure 4e) Mainly distributed in fine-grained regions (such as...) Figure 4 d and Figure 4 As shown in e), the nanoscale spherical Mg2Yb phase is discretely distributed; the alternating distribution of coarse and fine grain regions and the non-uniform distribution of the second phase result in a dual heterogeneous synergistic effect, giving the alloy a significant back stress strengthening effect; after isothermal hot extrusion at 295 °C and an extrusion speed of 1 mm / s with an extrusion ratio of 20:1, the Mg-Al-Yb-Zn alloy exhibits a room temperature tensile yield strength of 221 MPa, a tensile strength of 332 MPa, and an elongation after fracture of 30%.
[0029] Furthermore, a ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized in that: the as-cast alloy consists of α-Mg grains and island-like Mg particles covering the grain boundaries. 17 Al 12 The composition includes the Al3Yb phase dispersed at grain boundaries and within grains. Figure 4 a and Figure 4 b) The average grain size of the as-cast alloy is 179 μm; the grain boundaries of the solid-solution alloy are clear, and no coarse Mg was detected. 17 Al 12 The phase consists of irregularly shaped Al3Yb phases discretely distributed in the solid solution alloy, with an average grain size of 197 μm; the extruded microstructure has an average grain size of 8.13 μm in the coarse-grained region and 4.57 μm in the fine-grained region. Figure 4 c); The extruded microstructure contains blocky Al3Yb phases with an average size of 0.8 μm enriched in the fine-grained region ( Figure 4 d and Figure 4 (as shown in e) and spherical Mg with an average size of 120 nm 17 Al 12 Mutually( Figure 4 e), and spherical Mg2Yb phases with an average size of 40 nm discretely distributed in both coarse and fine grain regions; the extruded alloy exhibits a weak tilted basal texture, with a maximum extreme density of 6.35 mI / L (e). Figure 4 f); The maximum heterogeneous deformation induced stress was 172 MPa when the test was performed according to the above cyclic loading, unloading and reloading test method.
[0030] Phase analysis showed that the alloy obtained in Example 2 contained the same type of Al3Yb phase and β-Mg as in Example 1. 17 Al 12 Phases and Mg2Yb phases. Representative interface structures of the three typical second phases with the α-Mg matrix in Example 1 are shown below. Figure 2 d- Figure 2 f.
[0031] Furthermore, the preparation steps of this dual heterostructure ytterbium-magnesium alloy include the following: 1) Alloy smelting: Magnesium ingots are heated and melted in a resistance heating furnace under the protection of SF6 and CO2 mixed gas. Then, pure aluminum ingots are added at 700 ℃ according to the mass percentage of Al in the final alloy of 7.5%. The mixture is stirred for 3 min under flux protection to aid melting. Then, Mg-Yb master alloy is added at 720 ℃ according to the mass percentage of Yb in the final alloy of 0.8%. Finally, zinc ingots are added at 700 ℃ according to the mass percentage of Zn in the final alloy of 0.4%. The mixture is stirred for 3 min to aid melting. The mixture is held at 720 ℃ for 5 min, a covering agent is added, and the mixture is allowed to stand to allow the inclusions to settle. The mixture is then allowed to stand at 710 ℃ for 5 min, the slag is removed, and the ingots are cast. 2) Solution treatment: The above ingots were kept at 420 ℃ for 23 h under argon protection, and then cooled to room temperature with water after being taken out of the furnace; 3) Slow isothermal extrusion: The solution-treated billet is heated to 295 ℃ and held for 30 min. The billet is then subjected to isothermal hot extrusion at a speed of 1 mm / s with an extrusion ratio of 20:1. Before extrusion, the difference between the surface temperature of the billet and the set temperature of the extrusion cylinder is measured by an infrared thermometer and is no more than 5 ℃. After the extruded material is extruded from the mold, it is immediately water-cooled to room temperature.
[0032] Example 3
[0033] A ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized by the following composition by mass percentage: Al content 8.5%, Yb content 1.2%, Zn content 0.6%, and the balance being Mg and other unavoidable impurities; the extruded microstructure of the alloy has a dynamic recrystallized grain area fraction of 86.2%, and on the longitudinal section of the extruded material, coarse-grained and fine-grained regions are alternately distributed radially and extend along the extrusion direction (e.g., ...). Figure 5 (as shown in b and 5c); simultaneously, there are bulk Al3Yb phases with sizes ranging from submicron to micron and submicron-sized spherical Mg. 17 Al 12 The phase is mainly distributed in the fine-grained region (e.g. Figure 5 As shown in c), the nanoscale spherical Mg2Yb phase is discretely distributed; the alternating distribution of coarse and fine grain regions and the non-uniform distribution of the second phase create a dual heterogeneous synergistic effect, giving the alloy a significant back stress strengthening effect; after isothermal hot extrusion at 300 °C at an extrusion speed of 0.7 mm / s and an extrusion ratio of 20:1, the Mg-Al-Yb-Zn alloy exhibits a room temperature tensile yield strength of 237 MPa, a tensile strength of 349 MPa, and an elongation after fracture of 25.7%.
[0034] Furthermore, a ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase is characterized in that: the as-cast alloy consists of α-Mg grains and island-like Mg particles covering the grain boundaries. 17 Al 12The composition includes the Al3Yb phase dispersed at grain boundaries and within grains. Figure 5 a) The average grain size of the as-cast alloy is 168 μm; the grain boundaries of the solid-solution alloy are clear, and no coarse Mg particles were detected. 17 Al 12 The phase consists of irregularly shaped Al3Yb phases discretely distributed in the solid solution alloy, with an average grain size of 175 μm; the extruded microstructure has an average grain size of 6.13 μm in the coarse-grained region and 2.41 μm in the fine-grained region. Figure 5 b); The extruded microstructure contains bulk Al3Yb phases with an average size of 1.7 μm enriched in the fine-grained region (e.g., Figure 5 (as shown in c) and spherical Mg with an average size of 300 nm 17 Al 12 Phase; TEM observation and statistical analysis showed that the average size of the Mg2Yb phase was 15 nm, and it was discretely distributed in both coarse-grained and fine-grained regions. The extruded alloy exhibited a weak tilted basal plane texture, with a maximum extreme density of 5.89 mM ( Figure 5 d) The maximum heterogeneous deformation induced stress was 185 MPa when tested according to the above-mentioned cyclic loading, unloading and reloading test method.
[0035] Phase analysis showed that the alloy obtained in Example 3 contained the same type of Al3Yb phase and β-Mg as in Example 1. 17 Al 12 Phases and Mg2Yb phases. Representative interface structures of the three typical second phases with the α-Mg matrix in Example 1 are shown below. Figure 2 d- Figure 2 f.
[0036] Furthermore, the preparation steps of this dual heterostructure ytterbium-magnesium alloy include the following: 1) Alloy smelting: Magnesium ingots are heated and melted in a resistance heating furnace under the protection of SF6 and CO2 mixed gas. Then, pure aluminum ingots are added at 710 ℃ according to the mass percentage of Al in the final alloy of 8.5%. The mixture is stirred for 5 min under flux protection to aid melting. Then, Mg-Yb master alloy is added at 725 ℃ according to the mass percentage of Yb in the final alloy of 1.2%. Finally, zinc ingots are added at 710 ℃ according to the mass percentage of Zn in the final alloy of 0.6%. The mixture is stirred for 5 min to aid melting. The mixture is held at 720 ℃ for 10 min, a covering agent is added, and the mixture is allowed to stand to allow the inclusions to settle. The mixture is then allowed to stand at 700 ℃ for 8 min, the slag is removed, and the ingots are cast. 2) Solution treatment: The above ingots are held at 430 ℃ for 25 h under argon protection, and then cooled to room temperature by water after being taken out of the furnace; 3) Slow isothermal extrusion: The billet after solution treatment is heated to 300 ℃ and held for 30 min. The billet is then subjected to isothermal hot extrusion at a speed of 0.7 mm / s with an extrusion ratio of 20:1. Before extrusion, the difference between the surface temperature of the billet and the set temperature of the extrusion cylinder is measured by an infrared thermometer and is no more than 5 ℃. After the extruded material is extruded from the mold, it is immediately water-cooled to room temperature.
[0037] Comparative Example 1 This comparative example is a Mg-8.0 Al-0.5 Zn alloy without added Yb. Compared with Example 1, this comparative example is identical in all aspects except for the absence of a Mg-Yb master alloy, including melting, solution treatment, and slow isothermal extrusion processes.
[0038] Specifically, during alloy smelting, magnesium ingots are heated and melted in a resistance heating furnace under the protection of a mixed gas of SF6 and CO2. Then, pure aluminum ingots are added at 710 °C according to the final alloy's Al mass percentage of 8.0%, and stirred for 3 minutes under flux protection to aid melting. Subsequently, zinc ingots are added at 710 °C according to the final alloy's Zn mass percentage of 0.5%, and stirred for 5 minutes to aid melting. After holding at 720 °C for 10 minutes, a covering agent is added and the mixture is allowed to stand to allow inclusions to settle. After standing at 700 °C for 10 minutes, the slag is removed and the ingot is cast. The resulting ingot is held at 420 °C for 24 hours under argon protection, and then water-cooled to room temperature after being removed from the furnace. The solution-treated billet is then heated to 300 °C and held for 30 minutes, and isothermal hot extrusion is performed at a speed of 0.5 mm / s with an extrusion ratio of 20:1. The temperature difference between the surface of the billet and the set temperature of the extrusion cylinder before extrusion is no more than 5 °C. After the extruded material exits the die, it is immediately water-cooled to room temperature.
[0039] The comparative as-cast alloy mainly consists of α-Mg grains and a continuous network of Mg grain boundaries. 17 Al 12 Phase composition: No Al3Yb or Mg2Yb phases were detected; the average grain size in the as-cast state was 224 μm, and Mg... 17 Al 12 The average phase size was 14.55 μm. After solution treatment and slow isothermal extrusion, the extruded microstructure of this comparative example was relatively uniform, dominated by equiaxed crystals, with an average grain size of 9.28 μm and a dynamic recrystallization degree of 80.1%. The second phase was generally dispersed, without forming a banded grain heterostructure with alternating coarse and fine grain regions along the extrusion direction, nor were Al3Yb and Mg phases formed. 17 Al 12 The number density of the second phase in the fine-grained region is higher than that in the coarse-grained region, which is a selective distribution characteristic of the second phase.
[0040] The room temperature tensile yield strength along the extrusion direction of this comparative example is 167 MPa, the tensile strength is 283 MPa, and the elongation after fracture is 24.8%. Compared with this comparative example, the yield strength and tensile strength of the alloy obtained in Example 1 are increased to 230 MPa and 340 MPa, respectively, and the elongation after fracture remains above 20%. Tests were conducted using the same cyclic loading, unloading, and reloading methods as in the examples, and the maximum heterogeneous deformation-induced stress obtained was approximately 150 MPa, lower than that in Example 1. These results indicate that by using only the same solution treatment and slow isothermal extrusion process without adding Yb, it is difficult to form the grain-second phase dual heterogeneous structure defined in this invention, and it is also difficult to obtain the strong-plasticity matching effect described in Example 1.
[0041] Finally, it should be noted that the above embodiments are only used to more clearly illustrate the working principle and process of the present invention and do not limit the present invention. The present invention can also be applied to other Mg-Al-Yb-Zn magnesium alloys within the aforementioned composition range, and their processing principles and steps are no different from the above examples, so there is no need to repeat the examples. The present invention overcomes the technical disadvantage of existing magnesium alloy materials in that they cannot simultaneously achieve strength and plasticity. Through optimized design of alloying elements, supplemented by a targeted conventional short-process preparation process, a high-performance wrought magnesium alloy with the above-mentioned properties can be obtained. This method can prepare ytterbium-containing magnesium alloys with a dual heterostructure of grains and a second phase through conventional melting and casting, solution treatment, and hot extrusion processes, and obtain a yield strength of 220-240 MPa, a tensile strength of 330-350 MPa, and an elongation after fracture of 25-30%.
Claims
1. A ytterbium-containing magnesium alloy with a dual heterostructure of grains and a second phase, characterized in that, The alloy comprises, by mass percentage: Al 7.5-8.5%, Yb 0.8-1.2%, Zn 0.4-0.6%, with the balance being Mg and unavoidable impurities. The alloy has an extruded microstructure, exhibiting alternating fine-grained and coarse-grained regions extending along the extrusion direction on the longitudinal section of the extruded material. The average grain size in the fine-grained region is 2-5 μm, and the average grain size in the coarse-grained region is 6-8.5 μm. The second phase comprises submicron to micron-sized blocky Al3Yb phase and submicron-sized spherical Mg phase. 17 Al 12 Phase and nanoscale spherical Mg2Yb phase, in which Al3Yb phase and Mg 17 Al 12 The number density of the phase in the fine-grained region is higher than that in the coarse-grained region, and the Mg2Yb phase is dispersed in the matrix; the room temperature tensile yield strength of the alloy along the extrusion direction is not less than 220 MPa, the tensile strength is not less than 330 MPa, and the elongation after fracture is not less than 25%.
2. The ytterbium-containing magnesium alloy according to claim 1, characterized in that, The Al3Yb phase, Mg 17 Al 12 The average sizes of the phase and the Mg2Yb phase are 150 nm-2 μm, 100-500 nm and 10-50 nm, respectively.
3. The ytterbium-containing magnesium alloy according to claim 1, characterized in that, The recrystallized grain area fraction, determined by GOS≤2°, is greater than 85%; the alloy exhibits a tilted weak basal texture, with basal poles deviating from the center of the pole figure, and a maximum pole density of 5.5~6.5 mud.
4. The ytterbium-containing magnesium alloy according to claim 1, characterized in that, The Al3Yb phase forms a semi-coherent interface with the α-Mg matrix, with a lattice mismatch of 10%–13%; the Mg 17 Al 12 The Mg2Yb phase forms a coherent interface with the α-Mg matrix, with a lattice mismatch of 1% to 3%; the Mg2Yb phase forms a non-coherent interface with the α-Mg matrix.
5. The ytterbium-containing magnesium alloy according to claim 1, characterized in that, When the alloy is subjected to cyclic loading, unloading and reloading tensile tests along the extrusion direction at room temperature, the maximum heterogeneous deformation induced stress is 170-185 MPa.
6. A method for preparing the ytterbium-magnesium alloy according to claim 1, characterized in that, Includes the following steps: 1) Alloy smelting: Magnesium ingots are melted under the protection of a mixed gas of SF6 and CO2. Pure aluminum ingots are added at 700-710 ℃ according to the mass percentage of Al in the final alloy of 7.5-8.5%. The mixture is stirred for 3-5 min under flux protection. Then, Mg-Yb master alloy is added at 720-725 ℃ according to the mass percentage of Yb in the final alloy of 0.8-1.2%. Zinc ingots are then added at 700-710 ℃ according to the mass percentage of Zn in the final alloy of 0.4-0.6% and stirred for 3-5 min. The mixture is held at 720-725 ℃ for 5-10 min, a covering agent is added and the mixture is allowed to stand to allow the inclusions to settle. The mixture is then allowed to stand at 700-710 ℃ for 5-10 min, the slag is removed and the mixture is cast to obtain the ingot. 2) Solution treatment: The ingot is kept at 420-430 ℃ for 23-25 h under argon protection, and then water-cooled to room temperature; 3) Slow isothermal extrusion: Heat the solution-treated billet to 295-300 ℃ and hold for 30 min. Perform isothermal hot extrusion at an extrusion speed of 0.5-1 mm / s and an extrusion ratio of 20:
1. The difference between the surface temperature of the billet and the set temperature of the extrusion cylinder before extrusion is no more than 5 ℃. After the extruded material is demolded, it is water-cooled to room temperature.
7. The preparation method according to claim 6, characterized in that, Step 1) The average grain size of the as-cast ingot The grain size is 160–180 μm, and the average grain size after solution treatment in step 2) is 170–200 μm; OM and SEM observations showed no continuous network of Mg at the grain boundaries of the solution-treated alloy. 17 Al 12 Phase, residual Mg 17 Al 12 The average size of the phase is less than 1 μm.